Watch me on YouTube: A concept of CALL-TBLT to promote Indonesian EFL students’ communicative performance - Oktavia Widiastuti (University of Muhammadiyah Malang, 2025)
A pedagogical approach that enhances students' focus on language use for communication is Task-Based Language Teaching (TBLT). With the increasing significance of technology in educational environments, tasks mediated by computer-assisted language learning (CALL) present novel opportunities for acquiring foreign language skills and enhancing communicative performance. This study seeks to explore the application of cinematic speaking videos uploaded on YouTube within the framework of CALL enhanced-TBLT. This study employs a Research and Development model alongside a one-group pretest-posttest experimental design to detail the process students undergo in creating cinematic speaking videos and to assess the video's effectiveness in enhancing students' communicative performance. Data were collected using a questionnaire, an experts’ validation sheet, and a group pretest-posttest design. This investigation demonstrated that cinematic speaking videos enhanced students' communicative performance. The t-test results revealed t = 19.318 and p = 0.000, indicating a significant effect of the CALL-TBLT implementation. It provided students with the chance to engage with a genuine online audience and experience real-life communication through the YouTube platform. The interplay between the task and technology fosters reciprocal advantages: the task can be augmented by the capabilities of web 2.0 technologies, while computer-assisted language learning (CALL) offers distinctive benefits for language acquisition. Considering the study's findings, it is strongly recommended that further exploration into students' perceptions regarding the use of tasks and digital learning platforms with an online audience be conducted.